線維性異形成症に続発した下顎低悪性骨中心性骨肉腫の1例 - 小林, 正治; 西山, 秀昌; 程, 珺; 新垣, 晋; 芳澤, 享子; 金丸, 祥平 (日本口腔外科学会雑誌, 2018)
Sarcomatous transformation of fibrous dysplasia (FD) is an extremely rare event. We report a case of low-grade central osteosarcoma (LGCO), which arose secondarily from FD of the mandible. A 35-year-old woman, who had regularly been followed up for a 19-year period for a diagnosis of FD, presented with a painful swelling in right mandibular body. On computed tomographic images, the right mental area was prominently expanded with the eroded cortex, and its inner part was entirely filled with an inhomogeneously enhanced lesion. Since a biopsy specimen taken from the anterior lesion was diagnosed to be LGCO, a segmental mandibulectomy and reconstruction with a fibula free flap was performed. There has been no sign of recurrence or metastasis as of 7 years after surgery. It is important to make a diagnosis and a treatment plan in patients with FD because malignant transformation of FD occurs rather infrequently.